Assessing Women’s Participation in Nigerian Column Writing (Journal of Management and Social Sciences, 2021)
Journalism is a traditionally male-dominated profession. While women have made steady progress toward breaking their age-long under-representation in other key genres of Nigerian journalism, they remain largely sidelined in column writing. This paper compares the number of female columnists to that of their male counterparts. It also examines the predominant subjects of the listed female columns in order to see if their identified subjects potentially impact on the various agenda-setting and watchdog functions of the column and columnists. The researcher draws on the tenets of the agenda-setting and agenda-building theories of the mass media to establish that women can use the immense power of the column to shape public discourse and empower themselves. A content analysis of all the listed Nigerian columnists shows that the number of male columnists greatly outweighs that of the females. The study also shows that female columns are mainly about relationships and fashion. Therefore, women are urged to take advantage of the column, especially politics and economy columns, to advance the many issues of women’s rights as well as influence vital public discourse.KeywordsColumn writing, print media, columnists, agenda-setting, gender, content analysis